EXPERIMENTALLY ORIENTED MODEL OF EDUCATION IN LOWER SECONDARY EDUCATION IN THE SUBJECT OF TECHNOLOGY - KVASNOVA, Petra; DURIS, Milan (Trends in education, 2024)
The contribution is focused on the design and implementation of experiments in the education of students in lower secondary education in the subject of Technology. The current educational needs of pupils in the subject of Technology are primarily focused on practical activities and on the creative thought participation and cooperation of pupils, and for that reason we have focused on a model of education that is based on experimental starting points. Another need that must be met is the lowest possible financial burden on teachers when preparing the given experiments. For this reason, we focused on the experimental verification of the properties of materials using available materials and equipment that do not burden the budget of the school or the teacher.
Keywords: school experiment; subject Technique; model of education; primary school; formative assessment